From exploitation risks to mitigations: looking back locally on the implementation of the UK’s Ukraine Schemes - García Vázquez, Olaya; Cockbain, Ella; Roberts, Kate; Fisher, Oliver (My University, 2024)
.

This research project looks back on the implementation of the UK’s Ukraine humanitarian visa Schemes, with a focus on issues encountered around exploitation of displaced Ukrainians. It is based on research interviews conducted roughly seven to nine months on from the launch of the UK’s first Ukraine Scheme (Homes for Ukraine). This project builds upon a rapid assessment of human trafficking and exploitation risks and response needs in the UK linked to the war in Ukraine, in which major concerns were raised shortly after Russia’s full-scale invasion began1. This report summarises learning about Local Authorities’ responses to supporting displaced Ukrainians in the UK and how they were managing risks of trafficking and other exploitation across the various Ukraine Schemes. It is based on 26 interviews, conducted between October and December 2022 with representatives from Local Authorities (n=11), Strategic Migration Partnerships (n=3) and civil society organisations (n=12). We identified four main themes in terms of issues already encountered and factors widely seen to increase the risks of trafficking and exploitation among displaced Ukrainians in the UK. These are detailed below. Close attention should be paid to how the situation develops, and steps taken to mitigate these risks. The Westminster Government’s response to Ukrainian refugees contrasts sharply with its increasingly punitive approach to refugees and asylum seekers at large – although the Ukraine Schemes themselves have been suddenly and dramatically restricted as of February 2024. As our research shows, the protective functions of allowing people safe passage, the unrestricted right to work and access to public funds should not be underestimated. It is similarly vital to recognise the importance of being able to seek help if exploitation occurs, without fear of immigration detention and removal. From the perspective of attempts to prevent and respond more effectively to trafficking and exploitation, there are important lessons here for many other groups too.
Informe técnico